Understanding of the drug resistance mechanism of hepatitis C virus NS3/4A to paritaprevir due to D168N/Y mutations: A molecular dynamics simulation perspective. (December 2019) - Boonma, Thitiya; Nutho, Bodee; Rungrotmongkol, Thanyada; Nunthaboot, Nadtanet
Graphical abstract: Highlights: Effects of substitution of bulky side chain amino acids at position 168 which leads to a reduced inhibition activity of paritaprevir, were examined using MD simulation methodology. Mutation of D168Y was found to noticeably reduce ligand binding ability to the catalytic H57 besides the disruption of the R155···D168 salt-bridge formation. Mechanism underlying high-level resistance of paritaprevir against D168Y is possibly due to the loss of the R155···D168 salt-bridge formation and the decreased direct interaction with H57. The interactions with those of catalytic residues should be taken into account in order to design or to optimize HCV NS3/4A protease inhibitors. Abstract: Hepatitis C virus (HCV) NS3/4A protease is an attractive target for the development of antiviral therapy. However, the evolution of antiviral drug resistance is a major problem for treatment of HCV infected patients. Understanding of drug-resistance mechanisms at molecular level is therefore very important for the guidance of further design of antiviral drugs with high efficiency and specificity. Paritaprevir is a potent inhibitor against HCV NS3/4A protease genotype 1a. Unfortunately, this compound is highly susceptible to the substitution at D168 in the protease. In this work, molecular dynamics simulations of paritaprevir complexed with wild-type (WT) and two mutated strains (D168 N and D168Y) were carried out. Due to such mutations, the inhibitor-protein hydrogen bonding between them was weakened and the salt-bridge network among residues R123, R155 and D168 responsible for inhibitor binding was disrupted. Moreover, the per-residue free energy decomposition suggested that the main contributions from key residues such as Q80, V132, K136, G137 and R155 were lost in the D168 N/Y mutations. These lead to a lower binding affinity of paritaprevir for D168 N/Y variants of the HCV NS3/4A protease, consistent with the experimental data. This detailed information could be useful for further design of high potency anti-HCV NS3/4A inhibitors.